2020
DOI: 10.3390/coatings10010060
|View full text |Cite
|
Sign up to set email alerts
|

Transformations in CrFeCoNiCu High Entropy Alloy Thin Films during In-Situ Annealing in TEM

Abstract: In-situ TEM-heating study of the microstructural evolution of CrFeCoNiCu high entropy alloy (HEA) thin films was carried out and morphological and phase changes were recorded. Post annealing investigation of the samples was carried out by high resolution electron microscopy and EDS measurements. The film is structurally and morphologically stable single phase FCC HEA up to 400 °C. At 450 °C the formation of a BCC phase was observed, however, the morphology of the film remained unchanged. This type of transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Among HEAs, CoCrFeNiCu composition has been extensively studied earlier as HEA thin films and coatings deposited by magnetron sputtering [27,28], as volume HEA materials (mechanically alloyed powders and consolidated bulk samples) [29][30][31][32][33]. Different amounts of Ti and Al are usually added to study the phase evolution, mechanical and magnetic properties of designed systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among HEAs, CoCrFeNiCu composition has been extensively studied earlier as HEA thin films and coatings deposited by magnetron sputtering [27,28], as volume HEA materials (mechanically alloyed powders and consolidated bulk samples) [29][30][31][32][33]. Different amounts of Ti and Al are usually added to study the phase evolution, mechanical and magnetic properties of designed systems [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Their structure differed from that of as-cast bulk CoCrFeNiCu alloy used as a target; it was composed of two fcc phases, Cu-rich and Cu-depleted ones. Arfaoui et al [28] studied the sputtered single-phase fcc CoCrFeNiCu in thin films by in-situ TEM annealing. The structural and morphological stability of single-phase fcc HEA thin film was found stable up to 400°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al have found that thin films were composed of FCC grains with preferential (111) orientation as compared to as-cast Cu-CoCrFeNi HEAs where two FCC phases were detected (3.58 Å and 3.61 Å): a Cu-rich phase in interdendritic regions and a Cu-poor phase in dendritic morphology 37 . The in-situ annealing in TEM of Cu-CoCrFeNi thin films prepared by magnetron sputtering has been evaluated in 38 in the temperature range [673 K-973 K] for 5 min. Up to 673 K, a single FCC phase was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Annealing an HEA coating deposited by laser cladding has important impacts on its microstructure and wear resistance [17][18][19][20][21][22][23]. Ye et al [17] fabricated an Al x FeCoNiCuCr HEA coating on an AISI 1045 steel substrate by means of laser cladding.…”
Section: Introductionmentioning
confidence: 99%